Polyhedral oligomeric silsesquioxane-containing thiol-ene fibers with tunable thermal and mechanical properties - Fang, Yichen; Ha, Heonjoo; Shanmuganathan, Kadhiravan; Ellison, Christopher J. (ACS Applied Materials & Interfaces, 2016)
Polyhedral oligomeric silsesquioxanes (POSS) are versatile inorganic-organic hybrid building blocks that have potential applications as reinforcement nanofillers, thermal stabilizers, and catalyst supports for metal nano particles. However, fabrication of fibrous materials with high POSS content has been a challenge because of the aggregation and solubility limits of POSS units. In this paper, we describe a robust and environmentally friendly fabrication approach of inorganic-organic hybrid POSS fibers by integrating UV initiated thiol-ene polymerization and centrifugal fiber spinning. The use of monomeric liquids in this approach not only reduces the consumption of heat energy and solvent, but it also promotes homogeneous mixing of organic and inorganic components that allows integration of large amount of POSS (up to 80 wt %) into the polymer network. The POSS containing thiol-ene fibers exhibited enhanced thermomechanical properties compared to purely organic analogs as revealed by substantial increases in residual weight and a factor of 4 increase in modulus after thermal treatment at 1000 degrees C. This simple fabrication approach combined with the tunability in fiber properties afforded by tailoring monomer composition make POSS containing thiol-ene fibers attractive candidates for catalyst supports and filtration media, particularly in high-temperature and harsh environments.
Keywords: cross-linked fiber; enhanced thermomechanical properties; inorganic-organic hybrid fiber; POSS; reactive centrifugal spinning; thiol-ene photopolymerization

Piezoelectric energy harvesting from a ferroelectric hybrid salt [Ph3MeP](4)[Ni(NCS)(6)] embedded in a polymer matrix - Vijayakanth, Thangavel; Ram, Farsa; Praveenkumar, Balu; Shanmuganathan, Kadhiravan; Boomishankar, Ramamoorthy (Angewandte Chemie-International Edition, 2020)
Organic-inorganic hybrid ferroelectrics are an exciting class of molecular materials with promising applications in the area of energy and electronics. The synthesis, ferroelectric and piezoelectric energy harvesting behavior of a 3d metal ion-containing A(4)BX(6) type organic-inorganic hybrid salt [Ph3MeP](4)[Ni(NCS)(6)] (1) is now presented. P-E hysteresis loop studies on 1 show a remnant ferroelectric polarization value of 18.71 mu C cm(-2), at room temperature. Composite thermoplastic polyurethane (TPU) devices with 5, 10, 15 and 20 wt % compositions of 1 were prepared and employed for piezoelectric energy harvesting studies. A maximum output voltage of 19.29 V and a calculated power density value of 2.51 mW cm(-3) were observed for the 15 wt % 1-TPU device. The capacitor charging experiments on the 15 wt % 1-TPU composite device shows an excellent energy storage performance with the highest stored energies and measured charges of 198.8 mu J and 600 mu C, respectively.
Keywords: energy conversion; mechanical properties; non-covalent interactions; organic-inorganic hybrid composites; Phosphorus

PVDF/BaTiO3 films with nanocellulose impregnation: investigation of structural, morphological and mechanical properties - Ram, Farsa; Kaviraj, P.; Pramanik, R.; Krishnan, Amrutha; Shanmuganathan, Kadhiravan; Arockiarajan, A. (Journal of Alloys and Compounds, 2020)
Polyvinylidene fluoride (PVDF) composite films have witnessed widespread applications in biomedical and flexible electronic devices in recent years. These applications require a material that has enhanced electrical properties, mechanical flexibility along with sufficient strength. A lot of research has been carried out to enhance the piezoelectric and dielectric properties of the PVDF composite films. However, the improvements in the mechanical properties of nano filler reinforced PVDF composite films has not received due attention. In this regard, the present work focuses towards enhancing the mechanical strength and load-bearing capability of PVDF, by preparing composites of PVDF films impregnated with Cellulose Nanocrystals (CNC) and Barium Titanate (BTO) nanoparticles. Solution casting method was adapted to fabricate the PVDF/BTO/CNC films. X-ray diffractograms and FTIR (Fourier Transform infrared spectroscopy) corroborate the presence of ferroelectric gamma phase in PVDF. Mechanical and viscoelastic measurements have been carried out to examine the influence of CNC and BTO nano fillers in the PVDF matrix. The addition of CNC and BTO in PVDF film has improved the mechanical strength significantly. The stress achieved for PVDF/5% BTO and PVDF/5% BTO with 0.9% of CNC at 5% strain was 17% and 130% higher than the pristine PVDF, respectively. This study can be helpful for the design engineers to meet custom/specific requirements for a myriad of end- user applications such as piezoelectric nanogenerators. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: BaTiO3; Composite films; Mechanics; Morphology; Nanocellulose; PVDF